Community radio stations' production responses to COVID-19 pandemic in India. Issue 4 (17th September 2021) - Laskar, Kaifia Ancer; Bhattacharyya, Biswadeep
Abstract : The COVID-19 pandemic and the nationwide lockdown have made community radio broadcasting more important than before. Using case studies and interviews, we explored the kind of programming adopted by selected community radio (CR) stations in India during the pandemic and how they fight fake news. We also analyzed other issues they addressed during this period. We identified more dedicated programming services concerning COVID-19, fake news, and mental health using two-way communication by CR stations. The latter shared personalized and fact-checked information disseminated to the community. Issues related to rising domestic violence and mental health were also highlighted in their broadcast during the nationwide lockdown. Fake news percolated quickly in the communities where most members are illiterate and have little access to fact-checked information. CR stations indeed play a pivotal role in engaging the community in verifying fake news through personalized storytelling, using folk and traditional media, and engaging COVID-19 warriors from the community to authenticate the information.